Antioxidant Activity of Hybrid Sturgeon ( Huso dauricus × Acipenser schrenckii ) Protein Hydrolysate Prepared Using Bromelain, Its Fractions and Purified Peptides - Anwar Noman; Yuxia Wang; Chao Zhang; Sherif Abed (Polish Journal of Food and Nutrition Sciences)
Protein hydrolysates could be a natural and safer source of antioxidant peptides. The purpose of this study was to optimize the hydrolysis of Huso dauricus × Acipenser schrenckii sturgeon proteins using bromelain and purify antioxidant peptides from hydrolysate. The degree of hydrolysis of 18.69% was obtained under the optimal conditions and hydrolysate had 94.76% solubility, 902 nm particle size and high antioxidant activity. The IC 50 for DPPH • and ABTS •+ scavenging activity were 3.14 and 3.81 mg/mL, respectively. The fraction of hydrolysate with a molecular weight of <1 kDa exhibited the highest antiradical activity against DPPH • with IC 50 of 2.10 mg/mL. In turn, the IC 5 0 of the most active fraction after the Sephadex G-15 separation was 1.77 mg/mL. The reverse phase high performance liquid chromatography (RP-HPLC) was used to purify the peptides from this fraction. The peptide with histidine, leucine and glycine (MW of 0.2955 kDa) exhibited the highest antioxidant activity (IC 50 of 1.33 mg/mL). The obtained fractions and peptides with antioxidant activity could be used as natural substitutes for synthetic antioxidants, especially in food and pharmaceuticals.